Pengaruh Model Pembelajaran Creative Problem Solving terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Kadek Ana Lestari; Andinasari Andinasari; Dina Octaria (Universitas Sarjanawiyata Tamansiswa, 2021)
The purpose of this study was to determine the effect of the Creative Problem Solving (CPS) learning model on students' mathematical problem solving abilities at SMA Negeri 8 Palembang. This research method is a Quasi-experimental method with a Posttest-Only Control Design research design. The subjects in this study were students of class XI MIA 1 and XI MIA 2, SMA Negeri 8 Palembang, totaling 64 students. The instrument used in this study was a test of problem solving ability. Analysis of the data used in this study is the t test. The results showed that there was a positive influence on the application of the Creative Problem Solving (CPS) learning model to students' mathematical problem solving abilities.